2019
DOI: 10.1016/j.chb.2018.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Mobile ubiquity: Understanding the relationship between cognitive absorption, smartphone addiction and social network services

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
101
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(111 citation statements)
references
References 92 publications
(133 reference statements)
6
101
0
4
Order By: Relevance
“…. where highly engaging and engrossing experiences result in users' 'deep attention' and complete immersion and engagement with an activity" [25]. The multidimensional construct of CA has five dimensions: Temporal dissociation, focused immersion, heightened enjoyment, control, and curiosity, which follow closely with Griffiths' biopsychosocial model of addiction.…”
Section: Theories Adopted Across These Studiesmentioning
confidence: 88%
See 1 more Smart Citation
“…. where highly engaging and engrossing experiences result in users' 'deep attention' and complete immersion and engagement with an activity" [25]. The multidimensional construct of CA has five dimensions: Temporal dissociation, focused immersion, heightened enjoyment, control, and curiosity, which follow closely with Griffiths' biopsychosocial model of addiction.…”
Section: Theories Adopted Across These Studiesmentioning
confidence: 88%
“…This perspective focuses on the intrapersonal reasons a person may fall into SA, with positive attitudes potentially bringing about positive reinforcement to keep engaging in the cycle of excessive smartphone use. Other theories helping to illustrate user adoption and acceptance of information technologies include diffusion of innovations (Rogers, 1962), the theory of planned behavior (Ajzen, 1985), and the technology acceptance model (TAM) (Davis, 1989) [25].…”
Section: Theories Adopted Across These Studiesmentioning
confidence: 99%
“…Messaging apps have increased nomophobia, especially in teenagers, the age group most affected by this problem. Currently, the accelerating development of smartphones devices and the fact that they are easy to carry around all the time, means that mobile phones are replacing the internet as a primary addictive source [25]. In relation to gender, studies suggest that girls use their smartphones more often than boys and that their use is, therefore, more problematic [16].…”
Section: Risk Of Internet Addiction and Social Media Usementioning
confidence: 99%
“…1 The ability to access the internet and SNSs with a smartphone at all hours and locations renders excessive use especially facile. [2][3][4] Thus, excessive smartphone use bears further study, and there are several research gaps that can be identified.…”
Section: Introductionmentioning
confidence: 99%